(untitled) (Globalization and Business, 2023)
In today’s globalized, dynamic world, organizations’ dependence on information and, consequently, their interest and demands for information are growing. Information technologies play a crucial role in effective functioning and control for modern companies and businesses. In the conditions of operational accessibility of necessary information it is possible to adequate evaluation of current situation and to make timely decisions. At the same time, information must be available only to those to whom it is intended and unavailable - to all remaining. Computers are integrated into a common network for fast data transfer and efficient interaction. This connection must be reliable and secure. Modern companies are interested in the possibility of using Internet channels. However, the principles of building of the Internet give the chance to malefactors to steal and distort information purposely. Corporate and broadcasting networks which are based on TCP/IP protocols and are constructed on standard Internet applications (E-mail, Web, FTP) have no warranty from the invasion of unauthorized persons. In article the technology of creation of the virtual private networks (VPN), which is one of the optimal variants for creation of secure channel of communication, is considered.